ANALISIS STRATEGI PENDAMPINGAN GURU TERHADAP ANAK SLOW LEARNERS KELAS 2 SDN MORKEPEK - Alifia Filza Nabila; Serafim Kristianingsih; Jennie Salsabila Arfiyanti; Indi Helmia; Nova Estu Harsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe mentoring strategies in the learning process of students at SD Negeri Morkepek, particularly for those who experience slow learning. The mentoring strategies implemented include providing additional exercises, using learning methods tailored to students’ needs, involving peer support, and providing continuous motivation. The results of the study indicate that these strategies have a positive impact not only on improving academic abilities but also on the emotional and social development of students. The observed impacts include increased self-confidence, improved learning focus, the development of the ability to understand learning materials, increased participation in learning activities, and the maintenance of good social interactions among students. Therefore, appropriate mentoring strategies can help students optimize their potential and create a more comfortable and inclusive learning environment.